Characterization and evaluation of Greek tomato landraces for productivity and fruit quality traits related to sustainable low-input farming systems - Tagiakas, R. I.; Avdikos, I. D.; Goula, A.; Koutis, K.; Nianiou-Obeidat, Irini; Mavromatis, A. G. (Frontiers in Plant Science, 2022)
Tomato is one of the most important horticultural species all over the world, having high level of consumption and employing many people, both in the primary sector (farmers) and in the secondary sector (traders, seed companies and processors). Nowadays, the use of commercial tomato F1 hybrids tends to prevail because of high yield potential and homogeneity of fruits which are often characterized by lack of quality and sensory characteristics. In contrast, tomato landraces have outstanding quality traits, such as high concentration of antioxidants and organoleptic compounds, as well as often include desirable genes in their genome for adaptability, plasticity, response to low input conditions and high fruit nutritional value. Thus, they are appropriate material in the use of sustainable agricultural management systems or as gene donors for the development of new type of tomato cultivars suitable for low input farming systems. The present experimental study refers to 22 Greek tomato landraces and 2 commercial cultivars (cv. Macedonia and the F1 hybrid Formula) used as controls, which were characterized by phenotypical markers and evaluated under low input sustainable farming conditions. Specifically, during this research, measurements were taken regarding yield potential (early production, number of fruits per plant, fruit weight, total yield), fruit quality traits, such as physicochemical characteristics (pH, acidity, and soluble solid components - Brixο) also according to nutritional value (content of ascorbic acid, lycopene, total carotenoids and total phenolics) of tomato fruits. In the most promising landraces (cv. Milo Chalkidiki, cv. Eratiras, cv. Lotos, cv. Aspros lotos, cv. Pantaroza, cv. Karabola and cv. Kardia vodiou) having comparable yield and fruit quality traits with commercial cultivars, intrapopulation “Pure line selection” method, under low input farming conditions, was applied for two years. Following this approach, we succeed to determine the level of yield potential and provide information for the nutritive value and utilization of typical tomato landraces, improving their yield and fruit quality traits, following a mild intrapopulation selection under low input farming conditions. These data pipeline is expected to be of interest for organic farmers and processors of high nutritive tomato products, with low carbon footprint for the environment.